Parallel Omega Network Hash Construction - Wen Chuah, Chai; Abdullah, Nurul Azma (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Cryptography hash function is important to ensure data integrity when the data is transmitting in the insecure connections. Merkle-Damgård construction is the well-known architecture for most hash function algorithm. This construction will take arbitrary length of input and generate a fixed length of output which best known as hash value. The process of producing the hash value is executing sequentially. The implication of this is the computation time will increase linearly when the size of input increase. Therefore, an alternative architecture that can reduce the computation time when input size is increase is needed especially in the today world where multi-core processors and multithreading programming are common. Hence, in this research an alternative Parallel Omega Network Hash Construction that can execute in multi-core machine is proposed